Effect of heat/pressure on cyanidin-3-glucoside ethanol model solutions - Corrales Moreno, Margarita; Lindauer, Ralf; Butz, Peter; Tauscher, Bernhard (Journal of physics. Conference Series, 2008)
The stability of cyanidin-3-glucoside (Cy3gl) in 50% ethanol model solutions under heat/pressure treatments was investigated. Cy3gl was rapidly degraded when solutions were subjected to a heat/pressure treatment. The higher the pressure and the temperature used, the higher the degradation. Moreover, the degradation was increased according to increasing holding times. Parallel to the degradation of Cy3gl several hydrolytic products were formed and identified by LC-DAD/ESI-MS. The degradation of Cy3gl was well fitted to a first order reaction (R=0.99). This study pointed out the rate of susceptibility of Cy3gl in model solutions to degrade when exposed to a heat/pressure treatment and the trigger effect of high hydrostatic pressure to hydrolyse Cy3gl. By contrast, the degradation of anthocyanins in a food matrix (red grape extract solutions) was negligible after a heat/pressure process at 600MPa, 70°C during 1h (P >0.05).